Almost 1 in 5 South African adults have chronic pain: a prevalence study conducted in a large nationally representative sample. Issue 7 (July 2020) - Kamerman, Peter R.; Bradshaw, Debbie; Laubscher, Ria; Pillay-van Wyk, Victoria; Gray, Glenda E.; Mitchell, Duncan; Chetty, Sean
Abstract : Abstract: Limited information on the prevalence and risk factors for chronic pain is available for developing countries. Therefore, we investigated the prevalence of chronic pain and the association between this pain and various personal and sociodemographic factors by including questions in the South Africa Demographic and Household Survey 2016. The survey was conducted by face-to-face interviews with a nationally representative sample of the adult population (ages 15 and older, n = 10, 336). Chronic pain was defined as pain or discomfort that had been experienced all the time or on and off for 3 months or more. The prevalence of chronic pain was 18.3% (95% confidence interval [CI]: 17.0-19.7). Women were more likely than were men to have chronic pain (men = 15.8% [95% CI: 13.9-17.8]; woman = 20.1% [95% CI: 18.4-21.8]), and the prevalence of chronic pain increased from 11.3% (95% CI: 9.6-13.3) for the age range 15 to 24 years to 34.4% (95% CI: 30.6-38.4) for the age range over 65 years. The body sites affected most frequently were the limbs (43.6% [95% CI: 40.4-46.9]), followed by the back (30.5% [95% CI: 27.7-33.6]). This article presents the prevalence of chronic pain in the general population of a middle-income African country. These data give much needed insights into the burden of, and risk factors for, chronic pain in low-resource settings, and identify priority groups for intervention. Abstract : Supplemental Digital Content is Available in the Text.We investigated the prevalence of chronic pain in a representative sample of the adult population of South Africa. We found that chronic pain affected 18% of adults, with women and the elderly being worst affected significantly more frequently than were men and younger respondents.